Studi confraternali: orientamenti, problemi, testimonianze - Marina, Gazzini (Reti Medievali E-Book, 2009)
This book is a collection of articles by Italian and foreign scholars designed to offer an overview of the processes and issues involved in the history of the confraternity movement, as yielded by studies in the historical, social, legal, literary and artistic spheres in the course of the twentieth century. The articles deal with the historical context of western Europe, and more specifically with Italy, in the period comprised between the Middle Ages and the early Modern Age. The collection is divided into four sections: Individuals and groups, which explores the emergence of an interest in confraternity communities in disciplines addressing the history of social groups, of the rural world, of women and of young people. The legal and institutional framework deals with issues of legitimacy and institutional structure. The economics of charity analyses the relations between the confraternities and the hospital structures, the procedures for the administration of the assets, and the strategies of governance underlying the policies of aid of which the confraternities were the principal instrument. Finally, the section Theatrical, musical, artistic and documentary evidence is devoted to the sources that have handed down evidence of the operation of the confraternities.